2020
DOI: 10.1002/ehf2.13154
|View full text |Cite
|
Sign up to set email alerts
|

Ligand conjugated antisense oligonucleotide for the treatment of transthyretin amyloidosis: preclinical and phase 1 data

Abstract: Aims Amyloidogenic transthyretin (ATTR) amyloidosis is a fatal disease characterized by progressive cardiomyopathy and/or polyneuropathy. AKCEA-TTR-L Rx (ION-682884) is a ligand-conjugated antisense drug designed for receptor-mediated uptake by hepatocytes, the primary source of circulating transthyretin (TTR). Enhanced delivery of the antisense pharmacophore is expected to increase drug potency and support lower, less frequent dosing in treatment. Methods and results AKCEA-TTR-L Rx demonstrated an approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…The AKCEA-TTR-L Rx dosage regimen under investigation in phase 3 was selected on the basis of the pharmacodynamics and safety analyses of the phase 1 randomized placebo-controlled study in 47 healthy volunteers. AKCEA-TTR-L Rx dosed at 45 mg every 4 weeks produced a mean reduction from baseline in serum TTR of 86% after four doses and an absence of potential tolerability or safety issues, such as the increases in liver transaminase levels observed in the upper dose range of this study [ 29 ]. The GalNAc-mediated delivery of AKCEA-TTR-L Rx to hepatocytes supports low-dose therapy and a more convenient dosage regimen (i.e., monthly administration) relative to the unconjugated ASO therapy used for the treatment of hATTR-PN [ 22 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AKCEA-TTR-L Rx dosage regimen under investigation in phase 3 was selected on the basis of the pharmacodynamics and safety analyses of the phase 1 randomized placebo-controlled study in 47 healthy volunteers. AKCEA-TTR-L Rx dosed at 45 mg every 4 weeks produced a mean reduction from baseline in serum TTR of 86% after four doses and an absence of potential tolerability or safety issues, such as the increases in liver transaminase levels observed in the upper dose range of this study [ 29 ]. The GalNAc-mediated delivery of AKCEA-TTR-L Rx to hepatocytes supports low-dose therapy and a more convenient dosage regimen (i.e., monthly administration) relative to the unconjugated ASO therapy used for the treatment of hATTR-PN [ 22 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…AKCEA-TTR-L Rx is a GalNAc-conjugated ASO with a nucleotide sequence identical to inotersen, but with fewer phosphorothioate-modified internucleotide linkages, which is expected to improve its safety profile. Results from a first-in-human phase 1 study of AKCEA-TTR-L Rx in healthy volunteers demonstrated that AKCEA-TTR-L Rx 45 mg SC once every 4 weeks produced sustained decreases in serum TTR levels within 30 days of treatment initiation, achieving a mean reduction from baseline of 86% after four doses of treatment [ 29 ]. No treatment-related safety or tolerability issues were identified under this dosing regimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the improvements made to the tolerability profile of this set of 2¢MOE ASOs indicate the effectiveness of improvements made in Ionis' drug discovery and preclinical screening platform, which continues to evolve, as well as insights gained through clinical development of this class of ASOs. The potency and safety of many of the 2¢MOE-modified ASOs included in this analysis have been further improved by conjugation of the triantennary N-acetylgalactosamine (GalNAc 3 ) moiety for preferential and productive uptake by hepatocytes [27][28][29][30][31][32][33]. This enhancement in drug delivery increases ASO potency for RNA targets expressed by hepatocytes to support lower and less-frequent dosing, which upon integrated assessments may indicate a marked improvement in the tolerability profile for this emerging class of ASO drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Because glomerulonephritis and thrombocytopenia were reported as severe adverse events, close monitoring of platelet count and renal function is required in patients receiving inotersen. To improve the safety profile, a ligand-conjugated ASO of a nucleotide sequence identical to that of inotersen designed to facilitate receptor-mediated uptake by hepatocytes was also designed [122]. Currently, it is under investigation in phase III trials in ATTRv amyloidosis patients with polyneuropathy and ATTR patients with cardiomyopathy [122,123].…”
Section: Disease-modifying Therapiesmentioning
confidence: 99%